2017
DOI: 10.1007/s13203-017-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic condition boosts up the rate of phase transfer catalyzed polymerization of acrylonitrile in two-phase system

Abstract: An ultrasound condition associated with phasetransfer catalyst (PTC) has great diverse applications in synthesis of various organic and polymeric materials because of its fast reaction and high yield in short period of time. Phase transfer catalyst (cetyltrimethylammonium bromide as PTC) extracts the reactive radical anion from aqueous phase and transfer to organic phase whilst ultrasound condition enhances the radical formation; consequently, acrylonitrile was polymerized in ethyl acetate/ water two-phase sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
(88 reference statements)
0
3
0
3
Order By: Relevance
“…The thermodynamic parameters such as entropy of activation (ΔS # ), enthalpy of activation (ΔH # ) and free energy Table 1. The comparison of Ea value for different alkyl methacrylate under phase-transfer catalytic polymerization was reported [20,28,29]. The overall activation energy of 72.80 kJ/mol was reported for the polymerization of MMA using diphenyldisulphide and Cu (II) ion system [33].…”
Section: Role Of Temperature On R Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic parameters such as entropy of activation (ΔS # ), enthalpy of activation (ΔH # ) and free energy Table 1. The comparison of Ea value for different alkyl methacrylate under phase-transfer catalytic polymerization was reported [20,28,29]. The overall activation energy of 72.80 kJ/mol was reported for the polymerization of MMA using diphenyldisulphide and Cu (II) ion system [33].…”
Section: Role Of Temperature On R Pmentioning
confidence: 99%
“…It was found that the R p decreased in the following order: cyclohexanone > ethyl acetate > cyclohexane. An increase in the rate of polymerization was attributed to the increase in the polarity of the solvents, which facilitates greater transfer of peroxydisulfate ion from aqueous phase to organic phase [27][28][29] (Table 2).…”
Section: Role Of Organic Solvents Polarity On R Pmentioning
confidence: 99%
“…Murugesan et al employed cetyltrimethylammonium bromide as a phase transfer catalyst to polymerize the monomer acrylonitrile in an ethyl acetate/water system under ultrasound (25 kHz/300 W). [165] In the case, the reactive radical was powerfully produced with the aid of ultrasound, and then the anion was extracted from aqueous phase by cetyltrimethylammonium bromide and transferred to organic phase, so the polymerization rate was highly enhanced compared to the silent condition. As well, they completed the polymerization of N-vinyl carbazole under ultrasound by using a multi-site phase transfer catalyst (i.e.…”
Section: Polymerizationmentioning
confidence: 99%
“…Przykładem może być reakcja polimeryzacji akrylonitrylu prowadzona w układzie ciecz-ciecz wobec bromku cetylotrimetyloamoniowego (CTMAB) jako katalizatora PT (Rys. 9) [20]. Użycie ultradźwięków (25 kHz/300 W) spowodowało dwukrotne zwiększenie szybkości reakcji w porównaniu do reakcji bez ich udziału.…”
Section: Mechanizmy Katalizy Przeniesienia Międzyfazowegounclassified
“…Użycie ultradźwięków (25 kHz/300 W) spowodowało dwukrotne zwiększenie szybkości reakcji w porównaniu do reakcji bez ich udziału. Rolą katalizatora przeniesienia międzyfazowego jest transport reaktywnego anionu rodnikowego z fazy wodnej do fazy organicznej, podczas gdy ultradźwięki przyspieszają tworzenie się rodników [20].…”
Section: Mechanizmy Katalizy Przeniesienia Międzyfazowegounclassified